2018
DOI: 10.1155/2018/3947046
|View full text |Cite
|
Sign up to set email alerts
|

The Road Less Traveled in Elementary Physical Education: Exploring Human Relationship Skills in Adventure-Based Learning

Abstract: Teachers who are looking for ways to develop social and emotional learning with their students can use a curriculum model called Adventure-Based Learning (ABL). ABL consists of structured physical activities (cooperative in nature) with periods of reflection. e purpose of this study was to explore elementary physical education students' lived experience with intrapersonal and interpersonal relationship skills (IIRS) from an ABL unit of instruction. e aim of this study was to determine the credibility of an exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This is compounded by the lack of studies found that have explicitly and intentionally targeted SEL outcomes. Out of 63 studies reviewed, only four studies in K-12 PE settings utilizing student data explicitly aligned themselves with contemporary SEL terminology, outcomes, and frameworks (Escarti et al, 2018; Fernandez-Rio et al, 2017; Stuhr et al, 2015, 2018). While these studies are currently considered strong examples of school-based SEL research, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is compounded by the lack of studies found that have explicitly and intentionally targeted SEL outcomes. Out of 63 studies reviewed, only four studies in K-12 PE settings utilizing student data explicitly aligned themselves with contemporary SEL terminology, outcomes, and frameworks (Escarti et al, 2018; Fernandez-Rio et al, 2017; Stuhr et al, 2015, 2018). While these studies are currently considered strong examples of school-based SEL research, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies are currently considered strong examples of school-based SEL research, they are not without their limitations. For instance, Stuhr et al (2015, 2018) clearly focus on the competency of relationship skills in their respective studies. Fernandez-Rio et al (2017) primarily measured motivation, with disappointment and enjoyment emerging as themes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABL utilizes highly structured physical activities coupled with periods of group debriefing to promote social and personal development. Drawing on cooperative activities, ABL seeks to develop interpersonal and intrapersonal relationship skills to build a sense of community among students and teachers (Stuhr et al, 2018). ABL may also be well-suited to needs of children with ASD as it provides high amounts of opportunities to participate in PA at their own skill level and pace, without incessant pressure of competition and winning.…”
Section: Discussionmentioning
confidence: 99%
“…The literature in physical education positions ABL as a valid model-based practice (MBP) for social and emotional learning in K-12 physical education [3]. Based on this assertion, a properly conducted ABL curriculum is a well-founded and plausible way to promote a variety of desired social and emotional health outcomes for students [4,5].…”
Section: Introductionmentioning
confidence: 99%